2022
DOI: 10.3390/land11081280
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Awareness and Public Perception towards the Importance of Visual Aesthetics for Preservation of Permanent Forest Reserve (PFR) in Malaysia

Abstract: Malaysia has suffered a significant loss of forest cover over the years, mainly due to logging and land clearance for agriculture activities. Although the forest legislation has long been established and continuously enforced, it was not inclusive enough to protect the local natural resources. This study aims to identify public perception and awareness regarding values and essential aspects that affect the preservation of permanent forest reserves (PFR) in Malaysia. In particular, this study investigated the v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Reliability value The Cronbach's alpha test was employed to test the reliability of the variables used in assessing the perceived importance of ecosystem services and variable categories (Table 2 and Table 3). The reliability of these variables is based on the interpretation that a number or value closer to 1 indicates a highly reliable variable; otherwise, it shows lower reliability (Mundher et al, 2022). The Cronbach's alpha for all tested variables showed that their reliability is up to 0.98, above the 0.70 threshold level determined by Cronbach's (1951) alpha, thus indicating that the data used in this study are highly reliable.…”
Section: Resultsmentioning
confidence: 79%
“…Reliability value The Cronbach's alpha test was employed to test the reliability of the variables used in assessing the perceived importance of ecosystem services and variable categories (Table 2 and Table 3). The reliability of these variables is based on the interpretation that a number or value closer to 1 indicates a highly reliable variable; otherwise, it shows lower reliability (Mundher et al, 2022). The Cronbach's alpha for all tested variables showed that their reliability is up to 0.98, above the 0.70 threshold level determined by Cronbach's (1951) alpha, thus indicating that the data used in this study are highly reliable.…”
Section: Resultsmentioning
confidence: 79%
“…The experts emphasize the potential positive effects on local economies, but they also stress the need for a balanced approach between development and preservation to ensure sustainable economic growth and prevent negative consequences associated with excessive exploitation. In confirmation of that, Mundher et al [54] found that economic importance decreases when cutting down trees and the disappearance of natural landscapes, and vice versa, as economic importance increases when protecting natural landscapes.…”
Section: Experts' Perspectives On the Various Implications Of The Lac...mentioning
confidence: 78%
“…It will make a huge impact on political and social problems in the planning, management, and design of urban spaces. Furthermore, in the study to preserve Malaysian forests in order to increase aesthetics in this country, it was concluded that the aesthetic is reckoned a political-economic approach to preserving natural landscapes [19]. This opinion is so significant since the existence or extension of soft perspectives will make a sustainable landscape.…”
Section: E the Role Of Management And Planning In Making Beautifying ...mentioning
confidence: 99%